Digitalized urban transport system in small cities - Samadova, Konul (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Small cities face growing transport challenges due to urbanization and increasing mobility demands. Limited infrastructure and resource often hinder efficient transport management. Digitalization offers opportunities to enhance mobility, optimize routes, and improve commuter staus faction